2020
DOI: 10.3390/ijerph17186711
|View full text |Cite
|
Sign up to set email alerts
|

Objective Facts or Misleading Hype? Associations between Features of E-Cigarette Marketing and Sales on a Chinese E-Commerce Platform

Abstract: Background: Electronic cigarettes (e-cigarettes) have been increasingly advertised and marketed in China in recent years. This study examined the practice and impact of e-cigarette online marketing on a major retail website—Tmall.com. Methods: Data were obtained by crawling 449 online pages of e-cigarette marketing. Content analysis was conducted to summarize the marketing practices for four types of e-cigarettes, and multilevel modeling (MLM) was implemented to explore factors predictive of the online sales o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Extraverts are considered to be more sociable. Chen et al (1) found that e-cigarette sales advertisements in China mentioned that e-cigarette had social benefits such as promoting family harmony and establishing interpersonal relationships. Some studies have shown that smokers had higher extraversion scores than non-smokers (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extraverts are considered to be more sociable. Chen et al (1) found that e-cigarette sales advertisements in China mentioned that e-cigarette had social benefits such as promoting family harmony and establishing interpersonal relationships. Some studies have shown that smokers had higher extraversion scores than non-smokers (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, e-cigar in China is mainly sold to adolescents and young adults, so the online publicity platform has become the main point of sale. However, many e-cigar advertisements gave the wrong message, such as no nicotine, no addiction, can effectively help quit smoking, and arouse strong curiosity among college students (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations